Composite carbon fiber material, method for producing the same, composite carbon fiber structure, heat dissipating member, electronic product

CN122976124APending Publication Date: 2026-10-27BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510528871.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

聚丙烯腈(PAN)基碳纤维虽具备轻质特性(密度约1.8g/cm3),但其导热率普遍低于10W/(m·K),难以满足5G芯片、折叠屏铰链等高热流密度场景的需求

Benefits of technology

[0030]本发明第五方面提供一种电子产品,包括上述第四方面提供的散热部件,或上述第一方面的复合碳纤维材料,或上述第二方面的制备方法制得的复合碳纤维材料,或上述第三方面的复合碳纤维结构件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122976124A_ABST
    Figure CN122976124A_ABST
Patent Text Reader

Abstract

The application provides a composite carbon fiber material and a preparation method thereof, a composite carbon fiber structural member, a heat dissipation component and an electronic product. The composite carbon fiber material comprises N carbon fiber layers and M heat conduction layers, the carbon fiber layers and the heat conduction layers are arranged in an interlaced and laminated mode, N is greater than or equal to 1, and M is greater than or equal to 1; the heat conduction layer comprises a heat conduction layer substrate and heat conduction particles arranged on the surface of the heat conduction layer substrate. The composite carbon fiber material provided by the application has the in-plane isotropic heat conduction performance of the heat conduction layer substrate, and the heat conduction particles on the surface of the heat conduction layer substrate construct a three-dimensional hybrid heat conduction structure, so that the thickness direction heat conduction rate of the composite carbon fiber material is greatly improved. Therefore, the composite carbon fiber material has high heat conduction rates in the thickness direction and the horizontal direction, and is not prone to causing local heat accumulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon fiber material technology, and particularly relates to a composite carbon fiber material and its preparation method, composite carbon fiber structural components, heat dissipation components, and electronic products. Background Technology

[0002] With the rapid iteration and upgrading of electronic products, their internal heat flux density continues to rise, placing higher demands on thermally conductive materials, which are key heat dissipation components. Existing thermally conductive materials include polyacrylonitrile (PAN)-based carbon fiber and pitch-based carbon fiber. While PAN-based carbon fiber possesses lightweight properties (density approximately 1.8 g / cm³), its thermal conductivity is generally below 10 W / (m·K), making it difficult to meet the needs of high heat flux density applications such as 5G chips and foldable screen hinges. Pitch-based carbon fiber has a higher thermal conductivity than PAN-based carbon fiber, but it is prone to localized heat accumulation, affecting its overall thermal conductivity and thus limiting its application in electronic products.

[0003] Therefore, there is an urgent need to develop a carbon fiber material with good thermal conductivity and that is less prone to local heat accumulation. Summary of the Invention

[0004] This invention provides a composite carbon fiber material with high thermal conductivity in both the horizontal and thickness directions, making it less prone to localized heat accumulation.

[0005] This invention provides a method for preparing composite carbon fiber materials. The composite carbon fiber materials prepared by this method have high thermal conductivity in both the horizontal and thickness directions, making it less prone to local heat accumulation. Moreover, the preparation method is simple and easy to implement.

[0006] The present invention also provides a composite carbon fiber structural component, which has high thermal conductivity in both the horizontal and thickness directions.

[0007] The present invention also provides a heat dissipation component, which has excellent heat dissipation performance and can efficiently carry out multi-dimensional heat diffusion.

[0008] The present invention also provides an electronic product that has excellent stability and a long service life.

[0009] The first aspect of the present invention provides a composite carbon fiber material, comprising N carbon fiber layers and M thermally conductive layers, wherein the carbon fiber layers and the thermally conductive layers are staggered and stacked, N≥1, M≥1; the thermally conductive layer comprises a thermally conductive layer matrix and thermally conductive particles disposed on the surface of the thermally conductive layer matrix.

[0010] The composite carbon fiber material as described above, wherein the ratio of the thermal conductivity of the composite carbon fiber material in the thickness direction to that in the horizontal direction is 1:30-1.

[0011] In the composite carbon fiber material described above, the thermal conductivity of the thermally conductive particles is 30-3000 W / m². -1 K -1 ; and / or, the diameter of the thermally conductive particles is 0.1-1000 μm.

[0012] In the composite carbon fiber material described above, the thermally conductive particles account for 0.02-10% of the weight of the thermally conductive layer matrix.

[0013] In the composite carbon fiber material described above, the planar thermal conductivity of the thermally conductive layer matrix is ​​not less than 100 W / m. -1 K -1 .

[0014] In the composite carbon fiber material described above, the single-layer thickness of the carbon fiber layer is 0.02-2 mm; and / or, the single-layer thickness of the thermally conductive matrix is ​​0.01-10 mm.

[0015] The composite carbon fiber material as described above, wherein the thermally conductive particles include at least one of metallic materials, ceramic materials, and carbon materials; and / or, the thermally conductive layer matrix includes at least one of graphite film, graphene film, gold film, silver film, copper film, aluminum film, SiC film, boron nitride film, and alumina film; and / or, the carbon fiber layer includes a matrix and carbon fibers impregnated in the matrix.

[0016] The composite carbon fiber material as described above further includes a wetting agent located between the carbon fiber layer and the thermally conductive layer; the molecular weight of the wetting agent is 25-1000 g / mol.

[0017] The composite carbon fiber material as described above, wherein the wetting agent includes a cyanamide derivative.

[0018] In the composite carbon fiber material described above, the wetting agent accounts for 0.02-5% of the weight of the thermally conductive layer matrix.

[0019] The composite carbon fiber material described above, wherein the thermally conductive layer matrix has a hollow structure.

[0020] In the composite carbon fiber material described above, the hollow area in the hollow structure accounts for 0.2-10% of the total area of ​​the thermally conductive layer matrix.

[0021] A second aspect of the present invention provides a method for preparing a composite carbon fiber material, comprising:

[0022] 1) Introduce heat-conducting particles onto the surface of the heat-conducting layer substrate to obtain a heat-conducting layer;

[0023] 2) The thermally conductive layer and the carbon fiber layer are composited and cured to obtain the composite carbon fiber material.

[0024] In the preparation method described above, step 2) further includes heat treatment of the thermally conductive layer before the composite curing.

[0025] In the preparation method described above, the heat treatment temperature is 150-600℃ and the time is 0.5-6h.

[0026] The preparation method described above further includes wetting the thermally conductive layer before the composite curing.

[0027] In the preparation method described above, the wetting treatment includes introducing a wetting agent onto the surface of the thermally conductive layer.

[0028] A third aspect of this invention provides a composite carbon fiber structural component, comprising the composite carbon fiber material described in the first aspect, or the composite carbon fiber material prepared by the method described in the second aspect. Because the composite carbon fiber material has high thermal conductivity in both the thickness and horizontal directions, it is less prone to localized heat accumulation. Therefore, the composite carbon fiber plate exhibits good thermal conductivity in both the thickness and horizontal directions.

[0029] A fourth aspect of the present invention provides a heat dissipation component, comprising the composite carbon fiber structural component provided in the third aspect above, or the composite carbon fiber material of the first aspect above, or the composite carbon fiber material prepared by the preparation method of the second aspect above.

[0030] The fifth aspect of the present invention provides an electronic product comprising a heat dissipation component provided in the fourth aspect, or a composite carbon fiber material of the first aspect, or a composite carbon fiber material prepared by the preparation method of the second aspect, or a composite carbon fiber structural component of the third aspect.

[0031] The composite carbon fiber material provided by this invention comprises interleaved carbon fiber layers and a thermally conductive layer. The thermally conductive layer includes a thermally conductive layer matrix and thermally conductive particles on its surface. Because the thermally conductive layer matrix has in-plane isotropic thermal conductivity, and the thermally conductive particles on the surface of the matrix construct a three-dimensional hybrid thermally conductive structure, the thermal conductivity in the thickness direction of the composite carbon fiber material is significantly improved. Therefore, this composite carbon fiber material has high thermal conductivity in both the thickness and horizontal directions, making it less prone to localized heat accumulation. Attached Figure Description

[0032] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0033] Figure 1A schematic diagram of the composite carbon fiber material of the present invention: (a) N = 2, M = 1; (b) N = 3, M = 2;

[0034] Figure 2 This is a SEM image of thermally conductive particles deposited on the thermally conductive layer substrate in Embodiment 3 of the present invention;

[0035] Figure 3 The images show the infrared spectra of the original graphene and the infrared spectra of graphene and melamine in Example 2 of this invention.

[0036] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0038] Among existing thermally conductive materials, various carbon fiber materials, such as pitch-based carbon fiber, have high thermal conductivity, but they are prone to causing localized heat accumulation.

[0039] The inventors discovered through analysis that the reason for the local heat accumulation is that the thermal conductivity of the carbon fiber material is significantly anisotropic—it has a high thermal conductivity in the horizontal (fiber axis) direction, but a very low thermal conductivity in the thickness (perpendicular to the fiber axis) direction. This causes the "thermal channels" of the carbon fiber to extend only along the fiber axis direction and almost not in the direction perpendicular to the fiber axis, thus easily causing local heat accumulation.

[0040] Based on this, the first aspect of the present invention provides a composite carbon fiber material, including an N-layer carbon fiber layer and an M-layer thermally conductive layer, wherein the carbon fiber layer and the thermally conductive layer are staggered and stacked, N≥1, M≥1; the thermally conductive layer includes a thermally conductive layer matrix and thermally conductive particles disposed on the surface of the thermally conductive layer matrix.

[0041] The composite carbon fiber material provided by the present invention preferably has a unidirectional arrangement of carbon fibers in the carbon fiber layer, and the interlacing method of the carbon fibers can be at least one of plain weave, twill weave, satin weave, and braided weave.

[0042] In the composite carbon fiber material provided by this invention, N = 1, 2, 3, 4, or 5, and M = 1, 2, 3, 4, or 5. For example... Figure 1As shown in (a), N=2, M=1; as Figure 1 As shown in (b), N=3 and M=2.

[0043] It should be explained that the heat-conducting particles can cover at least a portion of the surface on one side of the heat-conducting layer substrate, or they can cover at least a portion of the surface on both sides of the heat-conducting layer substrate.

[0044] The composite carbon fiber material of this invention exhibits high thermal conductivity in both the horizontal and thickness directions, making it less prone to localized heat accumulation. This is due to two main reasons: First, the thermally conductive layer matrix itself possesses in-plane isotropic thermal conductivity. Using the thermally conductive layer matrix as a thermally conductive reinforcement, a continuous thermally conductive network is formed in both the X and Y directions of the horizontal plane, improving the thermal conductivity and mechanical properties of the composite carbon fiber material in both the horizontal (X and Y) directions. Second, the thermally conductive particles covering the thermally conductive layer matrix construct a three-dimensional hybrid thermally conductive structure, significantly increasing the thermal conductivity in the thickness direction (Z direction), thereby improving the ratio of thermal conductivity in the thickness to the horizontal direction of the composite carbon fiber material. Simultaneously, the thermally conductive particles have a protruding structure, which not only increases the specific surface area of ​​the thermally conductive layer matrix but also forms a mechanical interlocking structure with the carbon fibers through van der Waals forces, enhancing the interfacial bonding strength between the thermally conductive layer matrix and the carbon fiber layer. Therefore, the composite carbon fiber material of this invention exhibits high thermal conductivity in both the thickness and horizontal directions, making it less prone to localized heat accumulation.

[0045] In one specific embodiment, the ratio of the thermal conductivity of the composite carbon fiber material in the thickness direction to that in the horizontal direction is 1:30-1. Within this ratio range, the anisotropy of the composite carbon fiber material can be further reduced, making the composite carbon fiber material more widely applicable. Further, the ratio of the thermal conductivity of the composite carbon fiber material in the thickness direction to that in the horizontal direction is preferably 1:26.2-9.5.

[0046] For example, the ratio of the thermal conductivity of the composite carbon fiber material in the thickness direction to the horizontal direction is 1:30, 1:25, 1:20, 1:15, 1:10, 1:5 or 1:1, or a range of any two of these values.

[0047] In one specific embodiment, the thermal conductivity of the heat-conducting particles is 30-3000 W / m². -1 K -1 Within this range, the thermal conductivity of the thermally conductive particles can further improve the thermal conductivity of the composite carbon fiber material in the thickness direction, thereby resulting in high thermal conductivity of the composite carbon fiber material in both the fiber axis direction and the direction perpendicular to the fiber axis.

[0048] For example, the thermal conductivity of the heat-conducting particles is 30 W / m². -1 K -1 200Wm -1 K -1400Wm -1 K -1 600Wm -1 K -1 800Wm -1 K -1 1000Wm -1 K -1 1200Wm -1 K -1 1400Wm -1 K -1 1600Wm -1 K -1 1800Wm -1 K -1 2000Wm -1 K -1 2200Wm -1 K -1 2400Wm -1 K -1 2600Wm -1 K -1 2800Wm -1 K -1 Or 3000Wm -1 K -1 , or a range consisting of any two of the values.

[0049] In one specific embodiment, the diameter of the heat-conducting particles is 0.1-1000 μm. Heat-conducting particles with diameters within this range have lower interfacial thermal resistance and higher thermal conductivity during heat conduction.

[0050] For example, the thermal conductivity of the thermally conductive particles is 0.1 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm or 1000 μm, or a range of any two of these values.

[0051] In one specific embodiment, the thermally conductive particles account for 0.02-10% of the mass of the thermally conductive layer matrix. Within this range, the thermally conductive particles can better improve the thermal conductivity of the composite carbon fiber material in the thickness direction, and the carbon fiber layer and the thermally conductive layer are more tightly bonded and have better mechanical properties.

[0052] For example, the thermally conductive particles account for 0.02%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% of the weight of the thermally conductive layer substrate, or a range of any two of these values.

[0053] To further improve the thermal conductivity of composite carbon fiber materials, this invention controls the surface thermal conductivity of the thermally conductive layer matrix.

[0054] In one specific embodiment, the surface thermal conductivity of the thermally conductive layer substrate is not less than 100 W / m². -1 K -1 In this invention, the thermally conductive layer matrix is ​​a thermal conductivity enhancement material for carbon fiber, thus its high surface thermal conductivity further improves the thermal conductivity of the carbon fiber material.

[0055] For example, the surface thermal conductivity of the thermally conductive layer substrate is 100 W / m². -1 K -1 200Wm -1 K -1 400Wm -1 K -1 600Wm -1 K -1 800Wm -1 K -1 1000Wm -1 K -1 1200Wm -1 K -1 1400Wm -1 K -1 1600Wm -1 K -1 1800Wm -1 K -1 2000Wm -1 K -1 2200Wm -1 K -1 2400Wm -1 K -1 2600Wm -1 K -1 2800Wm -1 K -1 Or 3000Wm -1 K -1 etc., or a range consisting of any two of these values.

[0056] In one specific embodiment, the thickness of a single carbon fiber layer is 0.02-2 mm. Within this thickness range, the composite carbon fiber micromaterial exhibits higher thermal conductivity.

[0057] For example, the thickness of a single carbon fiber layer is 0.02 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, or 2 mm, or a range of any two of these values.

[0058] In one specific embodiment, the thickness of a single layer of the thermally conductive substrate is 0.01-10 mm. Within this range, the thermal conductivity of the composite carbon fiber micromaterial in the horizontal direction (X and Y directions) can be further improved.

[0059] For example, the thickness of the thermally conductive layer substrate is 0.01 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm, or a range of any two of these values.

[0060] To improve the thermal conductivity of composite carbon fiber micromaterials, the number of layers in the thermally conductive substrate can be further controlled, such as 1-9 layers.

[0061] To further improve the thermal conductivity of composite carbon fiber materials, this invention controls the types of thermally conductive particles, thermally conductive matrix, and carbon fiber layers.

[0062] In one specific embodiment, the thermally conductive particles include at least one of metallic, ceramic, and carbon materials. These thermally conductive particles all possess high thermal conductivity, which can better improve the thermal conductivity of the composite carbon fiber material in the thickness direction.

[0063] When the heat-conducting particles include multiple substances as described above, the present invention does not impose specific limitations on the proportions of the various substances.

[0064] Furthermore, the metallic materials include at least one of copper, gold, silver, and aluminum; the ceramic materials include at least one of alumina, silicon carbide, boron nitride, aluminum nitride, magnesium oxide, and magnesium nitride; and the carbon materials include at least one of fullerene, carbon powder, and diamond.

[0065] In one specific embodiment, the thermally conductive layer substrate includes at least one selected from graphite film, graphene film, copper film, aluminum film, SiC film, boron nitride film, and alumina film. The aforementioned thermally conductive layer substrate has higher surface thermal conductivity, which can better improve the horizontal thermal conductivity of the composite carbon fiber material.

[0066] When the thermally conductive layer substrate includes the aforementioned multiple substances, the present invention does not impose specific limitations on the proportions between the various substances.

[0067] To improve the bonding between the carbon fiber layer and the thermally conductive matrix, the raw materials in the carbon fiber layer are further controlled.

[0068] In one embodiment, the carbon fiber layer includes carbon fibers and a matrix coated on the carbon fibers.

[0069] The carbon fiber layer includes at least one of a polyacrylonitrile carbon fiber layer, a viscose-based carbon fiber layer, and a pitch-based carbon fiber layer. The thermally conductive layer matrix and thermally conductive particles of this invention can bond well with various carbon fiber layers, allowing for the preparation of different composite carbon fiber materials as needed.

[0070] When the carbon fiber layer includes multiple substances mentioned above, the present invention does not impose specific limitations on the proportions of the various substances.

[0071] The present invention does not specifically limit the weight ratio of carbon fiber to matrix. In one embodiment, carbon fiber accounts for 10-90% of the weight of matrix.

[0072] For example, carbon fiber accounts for 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90% of the weight of the matrix, or a range of any two of these values.

[0073] The present invention does not specifically limit the matrix composition in the carbon fiber layer, and conventional matrix compositions in the art can be used, such as at least one of epoxy resin, silicone resin, acrylic resin, polycarbonate resin, bismaleimide resin, phenolic resin, polyimide resin, and polyester resin.

[0074] In this invention, the carbon fiber layer includes carbon fiber prepreg, which includes at least one of polyacrylonitrile carbon fiber prepreg, viscose-based carbon fiber prepreg, and pitch-based carbon fiber prepreg.

[0075] To further enhance the bonding strength between the thermally conductive layer matrix and the carbon fiber layer, thereby improving the thermal conductivity of the composite carbon fiber material, a wetting agent can be introduced onto the surface of the thermally conductive layer matrix.

[0076] In one specific embodiment, the composite carbon fiber material further includes a wetting agent layer located between the carbon fiber layer and the thermally conductive layer; the molecular weight of the wetting agent in the wetting agent layer is 25-1000 g / mol. Wetting agents with molecular weights within this range can further enhance the adhesive strength between the thermally conductive layer matrix and the carbon fiber layer.

[0077] In one specific embodiment, the wetting agent includes a cyanamide derivative. Because the amino and cyano groups in the cyanamide derivative molecule can simultaneously form strong chemical bonds with the surfaces of metallic, ceramic, and carbon materials, and because the lone pair electrons of the nitrogen atom in the cyanamide group of the cyanamide derivative form coordinate bonds with the d orbitals of the metal, and the conjugated structure of the cyanamide group can form π-π conjugation with the d orbitals of the metal and the π bonds in the carbon material, the strong interaction between the cyanamide derivative and carbon, ceramic, and metallic materials can enhance the interfacial contact between the thermally conductive particles and the carbon fiber layer, and between the thermally conductive layer matrix and the carbon fiber layer, effectively improving thermal conductivity and adhesion strength. This molecular-level interface design allows for a reduction in the thickness of the composite carbon fiber material, with a minimum thickness of less than 0.2 mm, making it particularly suitable for ultra-thin devices such as mobile phones.

[0078] The present invention does not limit the specific types of cyanamide derivatives, such as at least one of monocyanamide, dicyandiamide, melamine, cyanamide ester derivatives, and cyanamide heteroatom-substituted derivatives.

[0079] The present invention does not impose a specific limit on the proportion of wetting agent to the weight of the thermally conductive layer substrate, and can be adjusted according to the actual situation.

[0080] In one specific embodiment, the wetting agent accounts for 0.02-5% of the weight of the thermally conductive layer substrate. Within this range, the wetting agent can better form a strong interaction force with the carbon fiber layer and the thermally conductive layer, enhance the interfacial contact between the carbon fiber layer and the thermally conductive layer, and effectively improve the thermal conductivity and adhesion strength.

[0081] For example, the wetting agent accounts for 0.02%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% of the weight of the thermally conductive layer substrate, or a range of any two of these values.

[0082] In one specific embodiment, the thermally conductive layer substrate has a perforated structure. This perforated structure allows the substrate on the carbon fiber layer to permeate into the perforated pattern through capillary action, further enhancing the bonding strength between the thermally conductive layer substrate and the carbon fiber layer. Furthermore, the perforated pattern is programmable and easily processed, allowing for flexible control of the thermal conductivity and strength properties of the composite carbon fiber material. By varying the pattern array arrangement and distribution density, unidirectional or bidirectional thermal conductivity, as well as high or low thermal conductivity characteristics, can be further achieved.

[0083] In one specific embodiment, the perforated area in the hollow structure accounts for 0.2-10% of the total area of ​​the thermally conductive layer substrate. Within this range, the bonding strength between the thermally conductive layer substrate and the carbon fiber layer is higher.

[0084] For example, the perforated area accounts for 0.2%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% of the total area of ​​the heat-conducting layer substrate, or a range of any two of these values.

[0085] The present invention does not specifically limit the hollow pattern in the hollow structure, for example, it can be at least one of dot matrix pattern, horizontal stripe array, and vertical stripe array.

[0086] A second aspect of the present invention provides a method for preparing a composite carbon fiber material, characterized in that it includes:

[0087] 1) Introduce thermally conductive particles onto the surface of the thermally conductive layer substrate to prepare a thermally conductive layer;

[0088] 2) The thermally conductive layer and the carbon fiber layer are composited and cured to prepare a composite carbon fiber material.

[0089] Specifically, in step 1), thermally conductive particles are introduced into the surface of the thermally conductive layer substrate to obtain the thermally conductive layer.

[0090] The present invention does not specifically limit the above-mentioned introduction method, and it can be at least one of physical vapor deposition, chemical vapor deposition, electroplating deposition, redox method, etc.

[0091] Furthermore, to facilitate the deposition of thermally conductive particles on the surface of the thermally conductive layer substrate, the thermally conductive layer substrate is cleaned. This invention does not specifically limit the cleaning method; it can be at least one of ultrasonic cleaning, mechanical scraping, plasma cleaning, acid washing, alkaline washing, and solvent cleaning.

[0092] Furthermore, to improve the bonding strength between the thermally conductive layer substrate and the carbon fiber layer, and to control the heat conduction path, a hollowed-out pattern is applied to the thermally conductive layer substrate. The improvement of the bonding strength between the thermally conductive layer substrate and the carbon fiber layer by the hollowed-out structure has already been explained above and will not be repeated here.

[0093] Through precise patterning, the heat conduction path can be directionally controlled. Periodic microstructure hollow patterns are fabricated on the thermally conductive layer substrate. For example, rectangular patterns with an aspect ratio of 100:1 can be processed along the X-axis on composite carbon fiber materials and uniformly distributed along the Y-axis. This results in the X-direction thermal conductivity exceeding that of the Y-direction by more than 10 times, and the X-direction tensile modulus exceeding that of the Y-direction by more than 1.5 times, achieving unidirectional thermal conduction in the X-direction and anisotropic mechanical properties. This customized design allows for a more rational layout of the device's heat dissipation structure. For example, in the mobile phone processor area, a high thermal conductivity channel in the X-direction can reduce the chip temperature by 18°C, while the Y-direction retains flexibility to adapt to structural deformation.

[0094] The present invention does not specifically limit the processing method of the hollow pattern, and it can be at least one of mechanical processing, laser engraving, chemical etching, and mask spin coating.

[0095] In step 2), the present invention does not specify the conditions for the composite curing of the thermally conductive layer and the carbon fiber layer; conventional composite curing conditions in the art can be used.

[0096] Preferably, the pressure for composite curing is 0.1-100 MPa, the temperature range is 40-200℃, and the time is 0.1-6 h.

[0097] For example, the pressure for composite curing is 0.1 MPa, 10 MPa, 20 MPa, 30 MPa, 40 MPa, 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa or 100 MPa, or a range of any two of these values.

[0098] For example, the curing temperature of the composite is 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, or a range of any two of these values.

[0099] For example, the curing time of the composite is 0.1h, 1h, 2h, 3h, 4h, 5h or 6h, or a range of any two of these values.

[0100] In one specific embodiment, step 2) further includes heat treatment of the thermally conductive layer before composite curing. Heat treatment of the thermally conductive layer is to relieve stress and further improve the bonding strength between the modified thermally conductive layer and the carbon fiber layer.

[0101] In one specific embodiment, the heat treatment temperature is 150-600°C and the time is 0.5-6 hours. Performing heat treatment within this temperature and time range can better eliminate stress.

[0102] In one specific embodiment, prior to composite curing, the thermally conductive layer is further wetted. Wetting the thermally conductive layer can further improve the bonding strength between the thermally conductive layer and the carbon fiber layer.

[0103] In one specific embodiment, the wetting process includes introducing a wetting agent onto the surface of the thermally conductive layer.

[0104] This invention does not specifically limit the method of introducing the wetting agent; for example, it can be introduced by spraying, applying, or soaking.

[0105] Specifically, the wetting agent can be dissolved in a solvent and then introduced onto the surface of the thermally conductive layer.

[0106] The present invention does not specifically limit the type of solvent for dissolving the wetting agent, and it can be at least one of water, ethanol, isopropanol, ethyl acetate, and acetone.

[0107] The present invention does not specifically limit the mass ratio of wetting agent to solvent, but preferably, the mass ratio of wetting agent to solvent is 0.2-40:100.

[0108] For example, the mass ratio of wetting agent to solvent is 0.2:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100 or 40:100, or a range of any two of these values.

[0109] Furthermore, the heat-conducting layer with the introduced wetting agent is dried. The present invention does not specifically limit the drying temperature and time, but preferably, the drying temperature is 40-80℃ and the drying time is 0.5-12h.

[0110] For example, the drying temperature is 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, or a range of any two of these values.

[0111] For example, the drying time is 0.5h, 1h, 3h, 5h, 7h, 9h, 11h or 12h, or a range of any two of these values.

[0112] A third aspect of the present invention provides a composite carbon fiber material structural component, comprising the composite carbon fiber material of the first aspect above, or the composite carbon fiber material prepared by the preparation method of the second aspect above.

[0113] The composite carbon fiber material structure includes composite carbon fiber material, so it has high thermal conductivity in both the horizontal and thickness directions, making it less prone to local heat accumulation.

[0114] A fourth aspect of the present invention provides a heat dissipation component, including the composite carbon fiber structural component provided in the third aspect above. Because the heat dissipation component includes the aforementioned composite carbon fiber structural component, it possesses excellent heat dissipation performance and can efficiently perform multi-dimensional heat diffusion.

[0115] This invention does not specifically limit the structure of heat dissipation components, such as heat sinks, heat fins, etc.

[0116] A fifth aspect of the present invention provides an electronic product including the heat dissipation component provided in the fourth aspect. Because the electronic product includes the aforementioned heat dissipation component, it exhibits excellent stability and a long service life.

[0117] This invention does not specifically limit the types of electronic products, such as smartphones, wearable devices, etc.

[0118] The composite carbon fiber material provided by the present invention will be described in detail below through specific embodiments.

[0119] Example 1

[0120] The composite carbon fiber material in this embodiment includes: two layers of unidirectional polyacrylonitrile carbon fiber prepreg, each layer with a thickness of 0.08 mm; and one layer of graphite film with a thickness of 20 μm and a surface thermal conductivity of 1000 W / m. -1 K -1 Fullerenes comprise 5% of the graphite film by weight, and their thermal conductivity is 30 W / m². -1 K -1 The diameter is 0.2 μm; melamine, a cyanamide derivative, accounts for 2% of the weight of the graphite film.

[0121] The method for preparing composite carbon fiber materials in this embodiment includes the following steps:

[0122] 1) Clean the graphite film surface with ethanol solvent to remove surface oil and dry it. Then, use laser engraving to create a perforated dot matrix pattern on the graphite film surface, resulting in a perforated graphite film. The spacing between adjacent dots is 1 cm, and the perforated pattern occupies 0.2% of the total area of ​​the graphite film.

[0123] 2) High thermal conductivity fullerene was deposited on the surface of the perforated graphite film by CVD, and then a melamine aqueous solution was sprayed on it. The mass ratio of melamine to water in the melamine aqueous solution was 10:100. After drying at 60°C, it was placed between two layers of polyacrylonitrile carbon fiber unidirectional prepreg. The composite carbon fiber material was obtained by constant temperature at 10MPa and 110°C for 0.5h.

[0124] Example 2

[0125] This embodiment is basically the same as Embodiment 1, except that:

[0126] After depositing high thermal conductivity fullerenes on the surface of the perforated graphite film by CVD, it is first placed in a vacuum sintering furnace and treated at 400℃ for 1 hour; then melamine aqueous solution is sprayed on it.

[0127] Example 3

[0128] This embodiment is basically the same as Embodiment 1, except that:

[0129] The fabric consists of 10 layers of woven polyacrylonitrile carbon fiber prepreg, each layer being 1 mm thick; and 9 layers of copper foil, each layer being 6 μm thick, with a planar thermal conductivity of 370 W / m². -1 K -1 Copper particles comprise 5% of the copper foil by weight, and the thermal conductivity of the copper particles is 350 W / m². -1 K -1 The diameter is 100 μm; the cyanamide derivative N-cyanothioimine accounts for 2% of the weight of the copper foil.

[0130] Preparation method:

[0131] The copper foil is patterned with perforated horizontal lines, with a spacing of 0.5cm between adjacent lines. The perforated pattern occupies 10% of the total area of ​​the copper foil.

[0132] After depositing copper particles on the surface of copper foil by electroplating, an N-cyanothioimine ethanol solution is sprayed on it. The mass ratio of N-cyanothioimine to ethanol in the N-cyanothioimine ethanol solution is 40:100. After complete wetting, the solution is dried at 80°C and placed between two layers of polyacrylonitrile carbon fiber woven prepreg. The composite carbon fiber material is obtained by maintaining a constant temperature of 120°C and 60MPa for 1 hour.

[0133] Example 4

[0134] This embodiment is basically the same as Embodiment 1, except that:

[0135] Two layers of pitch-based carbon fiber unidirectional prepreg, each 0.2 mm thick; one layer of graphene film, 150 μm thick, with a surface thermal conductivity of 1500 W / m. -1 K -1 Silver particles comprise 10% of the graphene film's weight, and their thermal conductivity is 420 W / m². - 1 K -1 The diameter is 4μm; the cyanamide derivative dicyandiamide accounts for 5% of the weight of the graphene film.

[0136] Preparation method:

[0137] The graphene film was patterned with a hollow dot matrix using a mask etching method, with an adjacent dot spacing of 0.4 cm and the hollow pattern accounting for 5% of the total area of ​​the copper foil.

[0138] After depositing silver particles on the graphene film surface by PVD, a dicyandiamide aqueous solution was spin-coated. The mass ratio of dicyandiamide to water in the dicyandiamide aqueous solution was 5:100. After complete wetting, the solution was dried at 80℃ and placed between two layers of pitch-based carbon fiber unidirectional prepreg. The composite carbon fiber material was obtained by constant temperature at 40MPa and 110℃ for 0.5h.

[0139] Example 5

[0140] This embodiment is basically the same as Embodiment 1, except that:

[0141] Two layers of polyacrylonitrile carbon fiber prepreg, each 0.1 mm thick; one layer of boron nitride film, each 2 mm thick, with a planar thermal conductivity of 270 W / m. -1 K -1 Diamond accounts for 0.04% of the weight of the boron nitride film, and the thermal conductivity of diamond is 2000 W / m². -1 K -1 The diameter is 20 μm; the cyanamide derivative melamine accounts for 0.05% of the weight of the boron nitride film.

[0142] Preparation method:

[0143] Diamond was grown on the surface of a boron nitride film by CVD, and then impregnated in a melamine aqueous solution with a melamine-to-water mass ratio of 5:100. After drying at 100°C, the material was placed between two layers of polyacrylonitrile carbon fiber prepreg and kept at 10 MPa and 100°C for 3 hours to obtain a composite carbon fiber material.

[0144] Example 6

[0145] This embodiment is basically the same as Embodiment 1, except that:

[0146] The diameter of the fullerene is 1200 μm.

[0147] Example 7

[0148] This embodiment is basically the same as Embodiment 1, except that:

[0149] Fullerenes account for 15% of the weight of the graphite film.

[0150] Example 8

[0151] This embodiment is basically the same as Embodiment 1, except that:

[0152] Do not spray melamine aqueous solution in step 2).

[0153] Example 9

[0154] This embodiment is basically the same as Embodiment 1, except that:

[0155] The cyanamide derivative melamine accounts for 10% of the weight of the graphite film.

[0156] Example 10

[0157] This embodiment is basically the same as Embodiment 1, except that:

[0158] In step 1), the graphite film is not perforated.

[0159] Example 11

[0160] This embodiment is basically the same as Embodiment 1, except that:

[0161] Fullerene particles account for 20% of the weight of the graphite film, and melamine, a cyanamide derivative, accounts for 4% of the weight of the graphite film.

[0162] High thermal conductivity fullerene particles were deposited on the surface of a graphite film by CVD. The treated graphite film was then sprayed with a melamine aqueous solution with a melamine to water mass ratio of 10:100. After drying at 60 degrees Celsius, the film was placed between two layers of carbon fiber prepreg and kept at 10 MPa and 110 degrees Celsius for 0.5 hours to obtain a composite carbon fiber material.

[0163] Example 12

[0164] This embodiment is basically the same as Embodiment 1, except that:

[0165] Fullerene particles account for 0.01% of the weight of the graphite film, and melamine, a cyanamide derivative, accounts for 0.01% of the weight of the graphite film.

[0166] High thermal conductivity fullerenes were deposited on the surface of a graphite film by CVD. The treated graphite film was then immersed in a melamine aqueous solution with a melamine-to-water mass ratio of 10:100. After complete wetting, the film was removed, dried at 60°C, and placed between two layers of carbon fiber prepreg. The film was then kept at 10 MPa and 110°C for 0.5 h. No composite carbon fiber material was obtained.

[0167] Comparative Example 1

[0168] Existing polyacrylonitrile carbon fiber sheets.

[0169] Comparative Example 2

[0170] Existing mesophase pitch-based carbon fiber boards.

[0171] Comparative Example 3

[0172] This comparative example is basically the same as Example 1, except that:

[0173] Fullerenes are not introduced into the graphite film.

[0174] Comparative Example 4

[0175] This comparative example is basically the same as Example 1, except that:

[0176] Composite carbon fiber materials were not obtained without introducing fullerenes and melamine into the graphite film.

[0177] Test case

[0178] 1. The composite carbon fiber materials prepared in the above examples and comparative examples were cut into composite carbon fiber plates with the same thickness; the thickness, thermal conductivity, and tensile strength of the composite carbon fiber plates were tested, and the test results are shown in Table 2; and the composite carbon fiber plate of Example 3 was subjected to SEM testing, and the results are shown in Table 2. Figure 2 The scale bar is 100 μm; infrared spectroscopy was performed on graphene and melamine in Example 2, and the results are shown in [the table below]. Figure 3 .

[0179] Depend on Figure 2 It can be seen that thermally conductive particles are deposited on the thermally conductive layer substrate.

[0180] Depend on Figure 3 As can be seen, compared with the infrared spectrum of the original graphene (before modification), the infrared spectra of graphene and melamine (after modification) in Example 2 show that at 1580 cm⁻¹... -1 The red shift and broadening of the peak indicate that there is a π-π conjugation effect between melamine and graphene.

[0181] 2. Testing Methods

[0182] 1) Thickness testing methods

[0183] Thickness testing was performed using a digital caliper according to GB / T 21389-2008 standard. Thickness measurements were taken from three or more areas of each sample, and the average value was calculated.

[0184] 2) Test method for thermal conductivity

[0185] Thermal conductivity was tested using a DRL-III thermal conductivity meter according to ASTM D5470-2006 standard, measuring the average thermal conductivity of the sample in the horizontal direction (X and Y directions) and the thickness direction (Z direction).

[0186] 3) Test method for tensile strength

[0187] The tensile strength of the sample was tested on a universal testing machine in accordance with the GB / T 1040.2-2006 standard, measuring the tensile strength in the horizontal X and Y directions.

[0188] Table 1

[0189]

[0190] Table 2

[0191]

[0192]

[0193] As shown in Table 1, compared with the comparative example, the composite carbon fiber material prepared by the present invention has better thermal conductivity in both the in-plane and thickness directions. This allows the composite carbon fiber material to achieve efficient heat dissipation in the horizontal direction and rapid heat transfer along the thickness direction when heated, making it less prone to local heat accumulation.

[0194] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.

Claims

1. A composite carbon fiber material, characterized in that, It includes N carbon fiber layers and M thermal conductive layers, which are staggered and stacked, with N≥1 and M≥1; the thermal conductive layer includes a thermal conductive layer matrix and thermal conductive particles disposed on the surface of the thermal conductive layer matrix.

2. The composite carbon fiber material according to claim 1, characterized in that, The ratio of the thermal conductivity of the composite carbon fiber material in the thickness direction to that in the horizontal direction is 1:30-1.

3. The composite carbon fiber material according to claim 1 or 2, characterized in that, The thermal conductivity of the heat-conducting particles is 30-3000 W / m². -1 K -1 ; and / or, the diameter of the thermally conductive particles is 0.1-1000 μm.

4. The composite carbon fiber material according to any one of claims 1-3, characterized in that, The thermally conductive particles account for 0.02-10% of the weight of the thermally conductive layer substrate.

5. The composite carbon fiber material according to any one of claims 1-4, characterized in that, The surface thermal conductivity of the thermally conductive layer substrate is not less than 100 W / m. -1 K -1 .

6. The composite carbon fiber material according to any one of claims 1-5, characterized in that, The thickness of a single layer of the carbon fiber layer is 0.02-2 mm; and / or the thickness of a single layer of the thermally conductive substrate is 0.01-10 mm.

7. The composite carbon fiber material according to any one of claims 1-6, characterized in that, The thermally conductive particles include at least one of metallic materials, ceramic materials, and carbon materials; and / or, the thermally conductive layer substrate includes at least one of graphite film, graphene film, gold film, silver film, copper film, aluminum film, SiC film, boron nitride film, and alumina film; and / or, the carbon fiber layer includes a substrate and carbon fibers impregnated in the substrate.

8. The composite carbon fiber material according to any one of claims 1-7, characterized in that, The composite carbon fiber material further includes a wetting agent layer, which is located between the carbon fiber layer and the thermally conductive layer; the molecular weight of the wetting agent in the wetting agent layer is 25-1000 g / mol.

9. The composite carbon fiber material according to claim 8, characterized in that, The wetting agent includes cyanamide derivatives.

10. The composite carbon fiber material according to claim 9, characterized in that, The wetting agent accounts for 0.02-5% of the weight of the thermally conductive layer substrate.

11. The composite carbon fiber material according to any one of claims 1-10, characterized in that, The thermally conductive layer substrate has a hollow structure.

12. The composite carbon fiber material according to claim 11, characterized in that, The hollowed-out area in the hollowed-out structure accounts for 0.2-10% of the total area of ​​the heat-conducting layer substrate.

13. A method for preparing the composite carbon fiber material according to any one of claims 1-12, characterized in that, include: 1) Introduce heat-conducting particles onto the surface of the heat-conducting layer substrate to obtain a heat-conducting layer; 2) The thermally conductive layer and the carbon fiber layer are composited and cured to obtain the composite carbon fiber material.

14. The preparation method according to claim 13, characterized in that, In step 2), before the composite curing, the thermally conductive layer is further subjected to heat treatment.

15. The preparation method according to claim 14, characterized in that, The heat treatment is performed at a temperature of 150-600℃ for a duration of 0.5-6 hours.

16. The preparation method according to claim 13, characterized in that, Before the composite curing, the thermally conductive layer is also wetted.

17. The preparation method according to claim 16, characterized in that, The wetting process includes introducing a wetting agent onto the surface of the thermally conductive layer.

18. A composite carbon fiber structural component, characterized in that, Includes the composite carbon fiber material according to any one of claims 1-12, or the composite carbon fiber material prepared by the preparation method according to any one of claims 13-17.

19. A heat dissipation component, characterized in that, It includes the composite carbon fiber structural component as described in claim 18, or the composite carbon fiber material as described in any one of claims 1-12, or the composite carbon fiber material prepared by the preparation method as described in any one of claims 13-17.

20. An electronic product, characterized in that, It includes the heat dissipation component as described in claim 19, or the composite carbon fiber material as described in any one of claims 1-12, or the composite carbon fiber material prepared by the preparation method as described in any one of claims 13-17, or the composite carbon fiber structural component as described in claim 18.